Islamic Entrepreneurship Management in the Era of Globalization: A Conceptual Review of the Experiences of Indonesia and Europe - S, Sugiharto; Syafa, Ananda; A, Azizah; Fauzan, A.; Dzaky, Naufal; Nifal, M.; Nurul, M. (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The conditions of entrepreneurial management in Indonesia and Europe show different but complementary dynamics in the context of modern business development. In Indonesia, entrepreneurship management is developing rapidly, driven by the growth of MSMEs, increased digital literacy, and government support through various incubation programs and access to financing. However, challenges remain in terms of management professionalization, long-term access to capital, and technological adaptability. Meanwhile, European countries generally have more established entrepreneurship management systems, characterized by strong innovation ecosystems, stable business regulations, and a strong research and development culture. Europe also excels in the implementation of sustainable management and the integration of Industry 4.0 technologies. A comparison of the two regions shows that Indonesia has significant potential through market growth and creative human resources, while Europe stands out for its mature and innovative management structures. Therefore, collaboration and knowledge exchange between the two regions have the potential to create more adaptive, innovative, and globally competitive entrepreneurship models.